O Território Do Brasil E Os Brasileiros Dos Livros Didáticos De Geografia - Gabrelon, Anderson [UNIFESP] (2017)
Some teaching procedures and situations that derive from the relationships lived in the school, contribute to the students to conceive Geography as a meaningless knowledge for their lives. The realization of this research was triggered by the uneasiness in understanding the meaning of teaching Geography. Based on this doubt the general purpose of the work was to analyze the identity of the territory of Brazil and the Brazilians of the textbooks of Geography, of the National Program of Textbook (PNLD), which are directed to the seventh year of elementary school. Our research object is the textbooks of Geography, highlighting two PNLD 2014 books, the Araribá Project and Geographic Expeditions, whose collections had the largest number of copies purchased by the State. In pursuit of the announced goal, we initially carried out a survey of the theses and dissertations that were concerned with the discourses of the Geography textbooks. We continue the research looking for didactic books that historically became reference to the teaching of the Brazilian Geography and these showed us a set of ideas, that we suspect are reproducing in the textbooks that are distributed in the schools through PNLD. Then we chose the primary sources of our analysis, we collected the data and simultaneously to the treatment of those, we were retrieving the theoretical references that supported the documentary analysis and the elaboration of the dissertation. The final analysis that was carried out for the closing of this work was based on the theories that based the data treatment, and it was compared the PNLD textbook samples and other textbooks of the Geography teaching trajectory. Among the theoretical foundations that served as input for our analysis, we have the works of researchers of Geography as Santos (2005), Silva (2006), Katuta (2007), Tonini (2013), Moreira (2014); Researchers in the history of the book, school subjects and curriculum among which Chervel (1990), Bittencourt (1993), Apple (1994), Chartier (1996), Munakata (1997), Choppin (2009), and other researchers such as Harley (1991) that works with the history of cartography; Lefebvre (1983) of the history of philosophy; Anderson (2008) of the History. Among the results of this dissertation we can verify the tradition that historically presents in Geography textbooks that record a fragmented reading of Brazil and do not signal the perspective of relating the parts (Nature-Man-Economy), an approach where the Brazilian is conceived separate from Nature and society. We understand that this way of looking at the territory and the nation disfavored the opening of a dialogue about the daily events of the students and that to understand the meaning of teaching Geography in the school will require an analysis of the meaning of this institution, like the other disciplines that constitute a curricular matrix, Geography is an area of knowledge that develops in relation to the internal reality of the school, building an autonomy that does not respond to what is done in the university.